Disparities in structural brain imaging in older adults from rural communities in Southern Nevada - Zhuang, Xiaowei; Cordes, Dietmar; Caldwell, Jessica Z. K.; Bender, Andrew R.; Miller, Justin B. (Frontiers in Aging Neuroscience, 2024)
INTRODUCTION: Identifying the associations between rural-living or neighborhood disadvantage and neurobiology may clarify rural-urban disparities in older adults with cognitive impairment related to Alzheimer’s disease. METHODS: We examined rural-urban differences and neighborhood disadvantages in brain cortical thickness (CT) measures among 71 rural and 87 urban-dwelling older adults. Analysis of covariance was used to test each FreeSurfer-derived CT measures’ associations with rural-urban living, clinical impairment status, and their interactions. Post-hoc linear regressions were used to test the association between CT measures and neighborhood disadvantage index. RESULTS: Rural-dwelling older adults had thinner cortices in temporal and inferior frontal regions compared to urban participants, especially among clinically normal participants, where the thinner temporal cortex further correlated with higher neighborhood disadvantage. Conversely, rural participants had thicker cortices in superior frontal, parietal and occipital regions. DISCUSSION: Our results suggest a complex interplay between community contexts and neurobiology. For memory-related regions, rural-living and neighborhood disadvantage might be negatively associated with subjects’ brain structures.